213k views
5 votes
1) 6a + 5a = −11

2)


−6


n − 2


n = 16

3)


4


x + 6 + 3 = 17 4) 0 =


−5


n − 2


n

5)


6


r − 1 + 6


r = 11 6)


r + 11 + 8


r = 29

7) −10 =


−14


v + 14


v 8)


−10


p + 9


p = 12

9) 42 =


8


m + 13


m 10)


a − 2 + 3 = −2

11) 18 =


3(


3


x − 6) 12) 30 =


−5(


6


n + 6)

-1-


13) 37 =


−3 +


5(


x + 6) 14) −13 =


5(


1 + 4


m) − 2


m

15)


4(





x + 4) = 12 16) −2 =


−(


n − 8)

17)


−6(


1 − 5


v) = 54 18) 8 =


8


v −


4(


v + 8)

19)


10(


1 + 3


b) = −20 20)


−5


n −


8(


1 + 7


n) = −8

21)


8(


4


k − 4) =


−5


k − 32 22)


−8(


−8


x − 6) =


−6


x − 22

23)


8(


1 + 5


x) + 5 =


13 +


5


x 24)


−11 −


5


a =


6(


5


a + 4)

1 Answer

9 votes

Answer:

6a + 5a = 11

6a + 5a=

11a

11a = 11

divide both side by 11

11a/11 = 11/11

a = 1

User Nulse
by
6.0k points